Perancangan Sistem Pengaturan Suhu pada Mesin Sangrai Kopi Berbasis Logika Fuzzy - Utomo, Satryo Budi; Agung, Moh.; Sumardi, Sumardi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2015)
One of commodity in Bondowoso district is a coffee. There are two coffee flavor i.e. arabica and robusta. The quality of coffee is depending on the roasting temperature of coffee. At constant temperature, it require long roasting time around 1,5 to 2 hours. Because of that, automatically temperature control system was needed to control the roasting temperature to make the roasting time faster and more efficient by using fuzzy logic method. Sugeno method was used in this study by inputing error temperature and âˆ† error temperature. The results show that temperature censor has 1.95% error against actual temperature of termometer. The fuzzy logic controls the actuator movement to regulate the valve of LPG that is fuel of furnace roaster. By using fuzzy logic, roasting time of arabica coffee and robusta coffee are 36,9 minutes and 30,216 minutes, respectively.